Obtainment of a highly concentrated pancreatic serine proteases extract from bovine pancreas by precipitation with polyacrylate - Lombardi, Julia (2013)
Serine proteases have wide application in leather, food, meat and soap powder industries, among others. There are a lot of methodologies to obtain them in large quantities but most of them are expensive or contaminating. We then propose an economical and environmentally friendly method in which proteases are separated from a crude fresh bovine pancreas homogenate using precipitation with polyacrylate, a commercially available negatively charged and weak polyelectrolyte. The zymogens of the serine proteases were activated prior to precipitation by the addition of trypsin. The proteases were precipitated by adding polyacrylate at pH 4.50 to the pancreas homogenate. Under these conditions, serine proteases are positively charged and form non-soluble complexes with the negatively charged polyacrylate. The purity of proteases was increased 5-fold with a recovery of 33% under the best conditions tested. The volume of the final product was decreased to 5% of the feedstock, in order to concentrate the sample up to 20 times. The proposed method removed up to 96% of the contaminant proteins.